1999
DOI: 10.1524/ract.1999.86.12.11
|View full text |Cite
|
Sign up to set email alerts
|

Excitation Functions for natW(p,xn)181-186Re Reactions and Production of No-Carrier-Added 186Re via 186W(p,n) 186Re Reaction

Abstract: Excitation functions were measured for the formation of l81 Re, 182m Re, 1828 Re, 183 Re, 184m Re, ,84e Re and 186 Re in proton-induced reactions on natural tungsten in the energy range of 7.5-22.5 MeV. The excitation function for 186 W(p,n)' 86 Re reaction has been obtained with maximum cross section value of 41.6 ± 6.2 mb at the proton energy of 9.2 MeV. 186 Re was produced from the reaction induced by 16 MeV protons on isotopically enriched 186 W metal powder target. Following the separation from 187 W, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 5 publications
1
11
1
1
Order By: Relevance
“…(5) [16]. It is clear that now the thick-target count rates fit the corrected summation of the thin-target yields, not only for our results but also for the data of Zhang et al [17], and even with small error to that of Moustapha et al [29]. However, Fig.…”
Section: Thin-target Vs Thick-target: Self-attenuation Correctionsupporting
confidence: 81%
See 1 more Smart Citation
“…(5) [16]. It is clear that now the thick-target count rates fit the corrected summation of the thin-target yields, not only for our results but also for the data of Zhang et al [17], and even with small error to that of Moustapha et al [29]. However, Fig.…”
Section: Thin-target Vs Thick-target: Self-attenuation Correctionsupporting
confidence: 81%
“…Recently a critical evaluation of the existing data was done using extensive nuclear model calculations by Hussain et al [9]. Besides pointing out many discrepancies in the data [2,[10][11][12][13][14][15][16][17], it was concluded that the use of highly enriched 186 W target material is absolutely necessary to produce high-purity 186g Re via the 186 W( p, n)-reaction, and that the energy of protons should be < 18 MeV [9].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [18] reported eight cross section values between 7 and 18 MeV. The beam monitor reactions used were the 63 Cu( p, 2n) 62 Zn and 65 Cu( p, n) 65 Zn processes and the data were taken from Grütter [51].…”
Section: Evaluation Of Data For the 186 W(p N) 186 Re Reactionmentioning
confidence: 99%
“…These reactions result in much higher specific activities, as the 186 Re is produced from a different element that can be chemically separated post-irradiation. Previously published investigations of high specific activity 186 Re production have utilized the 186 W(p,n) 186 Re or 186 W(d,2n) 186 Re reactions (Alekseev and Lazarev, 2006;Bonardi et al, 2010;Fassbender et al, 2013;Shigeta et al, 1996;Zhang et al, 2001;Zhang et al, 1999). It was concluded from those investigations that activation of 186 W by deuterons was preferred over protons as: (1) production yields are at least three time higher (Zhang et al, 2001), (2) the 186 Re radionuclidic purity is higher and remains higher (Alekseev and Lazarev, 2006;Zhu et al, 1997), and (3) lower quantities of enriched 186 W material are required for the irradiations.…”
Section: Introductionmentioning
confidence: 99%
“…The overall goal of this investigation was to demonstrate that production-levels of high specific activity 186 Re can be obtained via the (d,2n) reaction using thick W targets. Prior reported studies have used a variety of target materials for production of 186 Re, including W metal (Bonardi et al, 2010;Zhang et al, 2001;Zhang et al, 1999), WO 3 (Fassbender et al, 2013;Moustapha et al, 2006;Shigeta et al, 1996), Al 2 (WO 4 ) 3 (Zhu et al, 1997), and W carbides (Richards et al, 2015). However, those studies were limited to "thin" target bombardments or thick target investigations using only natural abundance target 3 material.…”
Section: Introductionmentioning
confidence: 99%